MEXICO AND THE FIFTH PAN-AMERICAN CONFERENCE: A DIPLOMATIC BATTLE FIELD AGAINST U.S. INTERVENTIONISM (Tzintzun, Revista de Estudios Históricos, 2016)
This article examines the indirect involvement of the Mexican government, headed by AlvaroObregon, in the fifth Conference of American States in Santiago, Chile in 1923.We review the positions the Mexican government took and the impact it had on the outcome of thatevent. During the conference the inter-American structure that the U.S. built since the latenineteenth century through its Pan American integration project was questioned. The criticismmade by a group of Latin American diplomats toward that structure was inspired by the exclusionthat the directors of the Pan American Union made of the Mexican government . The conferencewas therefore a diplomatic battle fiel against U.S. intervention in defence of the sovereignty of latinAmerican countries.
Keywords: Pan American; U.S. intervention; government recognition; sovereignty